Life Cycle Assessment of a system for the extraction and transformation of Waste Water Treatment Sludge (WWTS)-derived lipids into biodiesel - B. Notarnicola; G. Tassielli; P.A. Renzulli; R. Di Capua; F. Astuto; S. Riela; A. Nacci; M. Casiello; M.L. Testa; L.F. Liotta; C. Pastore (Science of The Total Environment, 2023)

Comparative transcriptomics implicates mechanisms of evolved pollution tolerance in a killifish population - A. WHITEHEAD; D. A. TRIANT; D. CHAMPLIN; D. NACCI (Molecular Ecology, 2010)
Wild populations of the killifish Fundulus heteroclitus resident in heavily contaminated North American Atlantic coast estuaries have recently and independently evolved dramatic, heritable, and adaptive pollution tolerance. We compared physiological and transcriptome responses to embryonic polychlorinated biphenyl (PCB) exposures between one tolerant population and a nearby sensitive population to gain insight into genomic, physiological and biochemical mechanisms of evolved tolerance in killifish, which are currently unknown. The PCB exposure concentrations at which developmental toxicity emerged, the range of developmental abnormalities exhibited, and global as well as specific gene expression patterns were profoundly different between populations. In the sensitive population, PCB exposures produced dramatic, dose‐dependent toxic effects, concurrent with the alterations in the expression of many genes. For example, PCB‐mediated cardiovascular system failure was associated with the altered expression of cardiomyocyte genes, consistent with sarcomere mis‐assembly. In contrast, genome‐wide expression was comparatively refractory to PCB induction in the tolerant population. Tolerance was associated with the global blockade of the aryl hydrocarbon receptor (AHR) signalling pathway, the key mediator of PCB toxicity, in contrast to the strong dose‐dependent up‐regulation of AHR pathway elements observed in the sensitive population. Altered regulation of signalling pathways that cross‐talk with AHR was implicated as one candidate mechanism for the adaptive AHR signalling repression and the pollution tolerance that it affords. In addition to revealing mechanisms of PCB toxicity and tolerance, this study demonstrates the value of comparative transcriptomics to explore molecular mechanisms of stress response and evolved adaptive differences among wild populations.

Genetic diversity and structure of an estuarine fish (Fundulus heteroclitus) indigenous to sites associated with a highly contaminated urban harbor - Amy M. McMillan; Mark J. Bagley; Suzanne A. Jackson; Diane E. Nacci (Ecotoxicology, 2006)